2022
DOI: 10.24154/jhs.v17i2.857
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield enhancement of carrot through integration of NPK and organic manures

Abstract: A pot experiment was conducted at Horticulture Experimental Area, Gomal University, Dera Ismail Khan, Pakistan to investigate the combined effects of NPK and organic manures on growth and yield of carrot, for two consecutive years. The experiment was laid out in CRD with six treatments and four replications. Five different organic manures such as poultry manure (PM), sewage sludge (SS), farmyard manure (FYM), press mud (PrM) and goat manure (GM) were applied in combination with NPK, each at recommended levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In contrast to our findings, a study from Mexico [28] reported significantly lower values of okra fruit weight (7.3-15.3 g). A lower AW was similarly reached in studies conducted in Pakistan [29] using 5 okra cultivars (8.2-10.1 g), India [30] using 7 cultivars (11.3-17.2 g), Egypt [31] using 5 cultivars (5.7-11 g) and Bangladesh [32] using 14 cultivars (14.0-17.8 g). In a study [33] in Nigeria using two cultivars, a higher AW of okra fruits was shown compared to previous studies (20.4-22.6 g).…”
Section: Average Weight Of Fruitssupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast to our findings, a study from Mexico [28] reported significantly lower values of okra fruit weight (7.3-15.3 g). A lower AW was similarly reached in studies conducted in Pakistan [29] using 5 okra cultivars (8.2-10.1 g), India [30] using 7 cultivars (11.3-17.2 g), Egypt [31] using 5 cultivars (5.7-11 g) and Bangladesh [32] using 14 cultivars (14.0-17.8 g). In a study [33] in Nigeria using two cultivars, a higher AW of okra fruits was shown compared to previous studies (20.4-22.6 g).…”
Section: Average Weight Of Fruitssupporting
confidence: 52%
“…Various studies with okra showed lower Y/P. In a study [29] in Pakistan, Y/P varied from 99.2 to 156.8 g, dependent on the okra cultivar. The Y/P (seven cultivars) ranged from 144.6 to 238.8 g in a study in India [30].…”
Section: Yield Per Plant and Hectarementioning
confidence: 90%